Diabetic foot wound care practices among patients visiting a tertiary care hospital in north India - Khan, Samreen; Srivastava, Anurag; Juneja, Khushboo; Rani, Reena (Indian Journal of Community Health, 2016)
Background: Diabetic foot syndrome is one of the most common and devastating preventable complications of diabetes resulting in major economic consequences for the patients, their families, and the society. Aims & Objectives: The present study was carried out to assess knowledge, attitude and practices of Diabetic Foot Wound Care among the patients suffering from Diabetic Foot and to correlate them with the socio-demographic parameters. Material & Methods: It was a Hospital based cross-sectional study involving clinically diagnosed adult (>18 years) patients of Diabetic Foot visiting the Surgery and Medicine OPDs at Teerthankar Mahaveer Medical College & Research Centre, Moradabad, India. Results: Significant association KAP (Knowledge, Attitude and Practices) score was seen with age of the patient, education, addiction, family history of Diabetes Mellitus, prior receipt of information regarding Diabetic foot-care practices, compliance towards the treatment and the type of foot wear used. Conclusions: The results highlight areas especially Health education, use of safe footwear and life style adjustments, where efforts to improve knowledge and practice may contribute to the prevention of development of Foot ulcers and amputation.